Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/1462-2920.13783
|View full text |Cite
|
Sign up to set email alerts
|

Success of chemolithoautotrophic SUP05 and Sulfurimonas GD17 cells in pelagic Baltic Sea redox zones is facilitated by their lifestyles as K‐ and r‐strategists

Abstract: Chemolithoautotrophic sulfur-oxidizing and denitrifying Gamma- (particularly the SUP05 cluster) and Epsilonproteobacteria (predominantly Sulfurimonas subgroup GD17) are assumed to compete for substrates (electron donors and acceptors) in marine pelagic redox gradients. To elucidate their ecological niche separation we performed S , NO3- and H CO3- stable-isotope incubations with water samples from Baltic Sea suboxic, chemocline and sulfidic zones followed by combined phylogenetic staining and high-resolution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…The pronounced, temporally complementary response to experimental manipulation of taxa affiliated with either Sulfurimonas or SUP05 support the existence of different niches occupied by the respective strains of these chemolithoauthotrophic organisms (Rogge et al ., ). The apparently higher oxygen tolerance of the SUP05 denitrification system may explain the spatial distribution of SUP05 and Sulfurimonas in the Baltic Sea redoxcline, where SUP05 members typically dominate over Sulfurimonas sp.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The pronounced, temporally complementary response to experimental manipulation of taxa affiliated with either Sulfurimonas or SUP05 support the existence of different niches occupied by the respective strains of these chemolithoauthotrophic organisms (Rogge et al ., ). The apparently higher oxygen tolerance of the SUP05 denitrification system may explain the spatial distribution of SUP05 and Sulfurimonas in the Baltic Sea redoxcline, where SUP05 members typically dominate over Sulfurimonas sp.…”
Section: Resultsmentioning
confidence: 97%
“…The apparently higher oxygen tolerance of the SUP05 denitrification system may explain the spatial distribution of SUP05 and Sulfurimonas in the Baltic Sea redoxcline, where SUP05 members typically dominate over Sulfurimonas sp. in the upper redoxcline while the opposite case is true in lower sulfidic redoxcline zones (Rogge et al ., ). Also the recently reported temporal shift from Sulfurominas to gammaproteobacterial sulfur oxidizer populations in the Cariaco Basin (Taylor et al ., ) could have been linked to such a niche differentiation in response to changing redox levels.…”
Section: Resultsmentioning
confidence: 97%
“…Given that sulfide oxidation spatially overlaps substantially with nitrate consumption (Fig. 4C), it is probable that nitrate is at least partly used as a terminal electron acceptor for the oxidation of various sulfur compounds, a process observed in other oxygen-depleted regions of the ocean (Canfield et al, 2010;Schunck et al, 2013;Louca et al, 2016;Rogge et al, 2017). Indeed, the Gammaproteobacterial clades BS-GSO2 and SUP05, members of which are frequently implicated in sulfide oxidation and denitrification in oxygen-poor marine systems (Lavik et al, 2009;Walsh et al, 2009;Fuchsman et al, 2012;Glaubitz et al, 2013;Shah et al, 2017;Rogge et al, 2017), have been observed at high relative abundances in the Cariaco Basin redoxcline (Rodriguez-Mora et al, 2015;Taylor et al, 2018;Suter et al, 2018).…”
Section: Metabolite Fluxes In Cariaco Basinmentioning
confidence: 99%
“…Given that sulfide oxidation spatially overlaps substantially with nitrate consumption (Figure 4c), it is probable that nitrate is at least partly used as a terminal electron acceptor for the oxidation of various sulfur compounds, a process observed in other oxygen-depleted regions of the ocean (Canfield et al, 2010;Louca et al, 2016;Rogge et al, 2017;Schunck et al, 2013). Indeed, the Gammaproteobacterial clades BS-GSO2 and SUP05, members of which are frequently implicated in sulfide oxidation and denitrification in oxygen-poor marine systems (Fuchsman, Murray, & Staley, 2012;Glaubitz, Kießlich, Meeske, Labrenz, & Jürgens, 2013;Lavik et al, 2009;Rogge et al, 2017;Shah, Chang, & Morris, 2017;Walsh et al, 2009), have been observed at high relative abundances in the Cariaco Basin redoxcline respectively. This pattern has been previously partly attributed to a "metal redox shuttle," whereby phosphate is scavenged during ferrous and manganese oxide formation in the redoxcline and subsequently redissolved at depth (Dellwig et al, 2010;McParland et al, 2015;Muller-Karger et al, 2019).…”
Section: Metabolite Fluxes In Cariaco Basinmentioning
confidence: 99%